Empowering Schools to Curb Teen Misconduct: The Role of Principals and Teachers - Madona, Putri; Akbar, Waza Karia; Wijaya, Wibi (Al-Qalam Institue, 2025)
Juvenile delinquency refers to actions that violate societal norms, rules, or laws, often stemming from unresolved conflicts and problems carried over from childhood into adolescence. In the school environment, such misconduct remains a recurring challenge for many educational institutions. This study aims to describe the roles of principals and teachers in addressing juvenile delinquency within schools. Employing a descriptive qualitative approach with a case study design, the research seeks to understand the lived experiences of research subjects, including their behaviors, perceptions, motivations, and actions. Informants were selected based on specific criteria, encompassing school administrators (principals, vice principals, and student affairs coordinators), homeroom teachers, guidance and counseling teachers, students involved in delinquent behavior, and their parents. Data were collected through observations, interviews, and document analysis. The findings emphasize that schools should serve not only as centers for academic learning but also as environments that foster moral and social values, equip students with essential life skills, and engage them in constructive activities that promote personal growth and responsible behavior.